Guidance and counseling profession: a philosophy and professional challenges in the future - Alfaiz, Alfaiz (COUNS-EDU: The International Journal of Counseling and Education, 2018)
As a science, guidance and counseling has become a helping profession that has been approved by society in the world, especially in academic and practical profession. In the begining, counseling was growth and developed in America which concern in how to place someone qualified with one work, this focus was to make a career decision through a counseling interview and assessmen, and also growth to help people to make decision and learn something new about them self in theraputic process, with psychological threatment and technique. As a multidicipliner science, counseling more flexible than any other dicipline. But in this 21 century counseling as a profession that has been challenges by something that must admit and counselor must know about this, such counseling multicultural, indigineous science that become an interesting subject, counseling has a value contract or not?, and counseling to educate and make client learn something or something that client found by them self? With liberate counseling?. This article will discuss more further about paradigm of guidance and counseling profession with point of view a philosophy and professional challenges in the future that must be understanding and face in the future without lose our cultural and religion values.